Action research in healthcare - Koshy, Elizabeth; Waterman, H. (Heather); Koshy, Valsa, 1945- (Los Angeles, Calif. : SAGE, 2011)
This is a practical guide to using research for improving practice in healthcare contexts. Taking you through the process step-by-step, the book explains how to tackle each stage of your project - from planning the study and undertaking a literature review, through to gathering and interpreting data and implementing findings.
Keywords: Health Services Research -- methods; Data Collection -- Methods; Quality Improvement; Research design